Wound Healing Using White Turmeric (Curcuma zedoaria) Extract Nanoparticles: Macroscopic and Microscopic ObservationWound Healing Using White Turmeric (Curcuma zedoaria) Extract Nanoparticles: Macroscopic and Mi - Ariyani, Fitri; Sutardi, Lina Noviyanti; Handharyani, Ekowati (Jurnal Veteriner; Vol 23 No 4 (2022)DO - 10.19087/jveteriner.2022.23.4.441, 2022)
A wound is damaged of skin tissue caused by physical or mechanical trauma. Naturally, the wound healing process begins almost immediately after the injury occurred and is categorized by four main stage, these are hemostasis, inflammation, proliferation, and maturation.  The aim of this research is to observe wound healing process using white turmeric (Curcuma zedoaria) nanoparticles extract gel based on macroscopic and microscopic observations. The skin of 24 Sprague dawley rats were cut 3 cm in the dorsal area and sutured with simple suture technique.  The treatments were divided into four groups, positive control (C1), negative control (C2), gel nanoparticles white turmeric extract 0.75% (K1) and 1.5% (K2).  Treatment was given every day for a week.  Macroscopically observation were made descriptively on the 1st, 3rd, 5th, and 7th days.  Histopatologically, the specimens were stained with hematoxylin eosin (HE) to observe the skin structure with parameters scab, epithelial formation, and neovascularization.  The observations were evaluated on the 8th days post-injury. Data were presented descriptively through light microscope.  The macroscopic results showed the nanoparticles extract gel treatment wound had a faster healing process and lower pain responses than the control groups. The microscopic showed the nanoparticles gel treatment extract had a better repairing process of skin structure and decreased inflammation cells than the control groups. In conclusion, the nanoparticles of white turmeric extract treatment gel group has a better results than the control groups.